Factors Related to Lymph Node Recurrence in Patients with N1b Papillary Thyroid Carcinoma after Unilateral Therapeutic Modified Radical Neck Dissection: A Meta-analysis - Su, Hui; Li, Yujie (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2018)
Background Papillary thyroid carcinoma with clinically node-positive lateral neck (N1b PTC) is likely to recur after modified radical neck dissection (MRND). The present study investigated the risk factors for recurrence in N1b PTC patients after unilateral therapeutic MRND.Methods Literature published from January 1990 to December 2017 on factors related to lymph node recurrence after MRND was retrieved by searching national and international online databases. A meta-analysis was performed after the data extraction process.Results Thirty-five potentially relevant articles were found on lymph node recurrence in patients with N1b papillary thyroid carcinoma. After careful review of the full text of these articles, seven studies were included. There was no association between recurrence and the age of the patients (OR = 1.28, 95% CI = 0.77 – 2.12, p = 0.34). Male patients (OR = 1.63, 95% CI = 1.17 – 2.27, p = 0.004), tumor size ≥ 1 cm (OR = 0.14, 95% CI = 0.03 – 0.76, p = 0.02), multifocal tumors (OR = 1.55; 95% CI = 1.08 – 2.22, p = 0.02), extracapsular invasion (OR = 1.92, 95% CI = 1.26 – 2.95, p = 0.003), and lymphovascular invasion (OR = 2.52, 95% CI = 1.50 – 4.22, p = 0.0005) were associated with a significantly higher incidence of recurrence.Conclusions Patients with a tumor size ≥ 1 cm, multifocality, extrathyroidal extension, or lymphovascular invasion were more likely to have tumor recurrence after total thyroidectomy and therapeutic MRND.
Keywords: cancer; surgical research; risk factor